IGF1R/IRS1 targeting has cytotoxic activity and inhibits PI3K/AKT/mTOR and MAPK signaling in acute lymphoblastic leukemia cells. (1st August 2019) - Rodrigues Alves, Ana Paula Nunes; Fernandes, Jaqueline Cristina; Fenerich, Bruna Alves; Coelho-Silva, Juan Luiz; Scheucher, Priscila Santos; Simões, Belinda Pinto; Rego, Eduardo Magalhães; Ridley, Anne J.; Machado-Neto, João Agostinho; Traina, Fabiola
Abstract: The IGF1R/IRS1 signaling is activated in acute lymphoblastic leukemia (ALL) and can be targeted by the pharmacological inhibitors NT157 (IGF1R-IRS1/2 inhibitor) and OSI-906 (IGF1R/IR inhibitor). Here we investigate the cellular and molecular effects of NT157 and OSI-906 in ALL cells. NT157 and OSI-906 treatment reduced viability, proliferation and cell cycle progression in ALL cell lines. Similarly, in primary samples of patients with ALL, both OSI-906 and NT157 reduced viability, but only NT157 induced apoptosis. NT157 and OSI-906 did not show cytotoxicity in primary samples from healthy donor. NT157 and OSI-906 significantly decreased Jurkat cell migration, but did not modulate Namalwa migration. Consistent with the more potent effect of NT157 on cells, NT157 significantly modulated expression of 25 genes related to the MAPK signaling pathway in Jurkat cells, including oncogenes and tumor suppressor genes. Both compounds inhibited mTOR and p70S6K activity, but only NT157 inhibited AKT and 4-EBP1 activation. In summary, in ALL cells, NT157 has cytotoxic activity, whereas OSI-906 is cytostatic. NT157 has a stronger effect on ALL cells, and thus the direct inhibition of IRS1 may be a potential therapeutic target in ALL. Highlights: IGF1R/IRS1 pathway contributes to the acute lymphoblastic leukemia pathogenesis. Preclinical characterization of NT157 and OSI-906 in acute lymphoblastic leukemia. NT157 exerts cytotoxic activity in acute lymphoblastic leukemia cells. OSI-906 presents cytostatic effect in acute lymphoblastic leukemia cells. Targeting IGF1R/IRS1 axis is potential therapeutic in acute lymphoblastic leukemia.